The Influence of Sharia Financial Literacy, Religiosity, and Perception of Saving Students’ Interest in Sharia Banks - Ilfita, Khoiriyah; Canggih, Clarashinta (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2021)
People in Indonesia in saving activities in sharia banks are still classified in the lower category than conventional banks. It is caused by several factors. Sharia financial literacy, religiosity and perceptions can be factors influencing people's interest in saving at sharia banks. This study aimed to determine the effect of sharia financial literacy, religiosity, and perceptions of saving interest in sharia banks. This study used a quantitative approach. In this research, researchers took samples used random sampling techniques. The data analysis technique used is multiple linear regression using the SPSS program. The results showed that partially sharia financial literacy had no effect on students' interest to save at sharia banks. While religiosity and perception partially have a positive and significant effect on students' interest to save in sharia banks. Simultaneously, sharia financial literacy, religiosity, and perceptions influence the interest of students to save in sharia banks.